2019
DOI: 10.3390/ijerph16142603
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Income after an Industrial Accident According to Industry and Return-to-Work Status

Abstract: Objective: To investigate changes in the incomes of workers, particularly those in the construction sector, who experienced industrial accidents according to their status of return to work. Methods: We used data from the fifth Panel Study of Workers’ Compensation Insurance. A repeated measures ANOVA was used to compare annual differential incomes before and after the industrial accident, and a linear mixed model was used to investigate the changes in income from before to after the industrial accident accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…In particular, the return-to-original-work rate among construction workers after an occupational injury was lower than among manufacturing and service workers. This was likely due to a higher percentage of daily workers in the construction industry than in the manufacturing and service industries [ 4 , 38 ]. In addition, most construction workers were older and thus more likely to have a disability after a workplace accident [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the return-to-original-work rate among construction workers after an occupational injury was lower than among manufacturing and service workers. This was likely due to a higher percentage of daily workers in the construction industry than in the manufacturing and service industries [ 4 , 38 ]. In addition, most construction workers were older and thus more likely to have a disability after a workplace accident [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…If workers suffered any mental or physical disability from occupational-related injuries or diseases and met the requirements for industrial accident compensation, they were assigned a disability rating from Grades 1 to 14 under the Korean Industrial Accident Compensation Insurance Act. A grade close to Grade 1 indicates a more serious disability [ 4 , 28 ]. Occupational injuries were classified into three categories: 1–7 (severe), 8–14 (moderate), and “none.”…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research found that the income of injured workers dropped by an average of 14% during the 5 years after an occupational accident in Korea. 9 In addition, a study on return to work of occupationally injured workers revealed that only half of them returned to work within 12 months, and around 20% still had no job at the time of 3 years after the accident. 3 Furthermore, socioeconomically disadvantaged groups at the time of accident experienced more loss of income; for example, daily workers’ income dropped by 27% while permanent workers’ income decreased by 7% during the 5 years after the accident.…”
Section: Discussionmentioning
confidence: 99%
“…3 Furthermore, socioeconomically disadvantaged groups at the time of accident experienced more loss of income; for example, daily workers’ income dropped by 27% while permanent workers’ income decreased by 7% during the 5 years after the accident. 9 This discrepancy might be a factor explaining the higher suicide risk among temporary workers than permanent workers.…”
Section: Discussionmentioning
confidence: 99%